Transmitting the spirit in missions: the history and growth of the Church of Pentecost - Markin, Amos Jimmy (Wipf & Stock, 2019)
Introduction: Christianity, mission, and Pentecostalism in Ghana -- Pentecostalism in Ghanaian Christianity -- A post-independence history of the Church of Pentecost -- Mission and growth in the Church of Pentecost: a case study of African Pentecostalism -- The Church of Pentecost International Missions: exemplary African Pentecostal missionary enterprise -- "Spirit and mission" - toward a theology of Pentecostal growth in Africa.